Legal protection of migrant workers and their families: before, during, and after working - Kartono Kartono; Siti Kunarti; Sri Hartini; Supriyanto Supriyanto; Dyah Adriantini Sintha Dewi (Borobudur Law Review, 2022)
This study aims to identify and analyze local government role as well as solving the problem concerning protection of migrant workers and their families before, during, and after working. The results showed that the local governments have not perfomed their role in maximum level to protect migrant workers and their families. Many policies have not been able to encourage legal protection because they are established on the old laws and emphasized administrative. The policies opens for brokers to operate in the village and the number of fake documents. The legal protection for migrant workers and their families is mainly provided by NGOs and individuals who are aware of protecting the migrant workers, and by establishing village regulations. It is necessary to initiate a more comprehensive legal protection, both administratively and technically through adjustment of local regulations to the new laws. In addition, the role of villages and communities/individuals can be expanded to better protect migrant workers.